Quitosana na indução de resistência ao tombamento de plântulas de espécies olerícolas e no controle de fitopatógenos in vitro - Rocha, Rita de Cassia Dosciatti Serrão (2015)
Induction of resistance is defined as the activation of a state of resistance against diseases which is induced systemically in plants by the use of biotic or abiotic agents without any modification of the plant genome, occurring non-specific way, by activating genes coding for various plant defense responses. Chitosan is a polymer derived from the deacetylation of chitin, which is found in large quantities in crustacean shell, and studied with the potential to control plant pathogens, both by its direct fungistatic action, as the ability to induce protection of plants, indicating the presence of molecules of elicitoras characteristics. Three experiments with objective of evaluating the potential of chitosan in the seedling resistance induction were developed, beet (Beta vulgaris) seeds, cucumber (Cucumis sativus) seeds and tomato (Solanum lycopersicum) seeds, and the control of Fusarium sp., Rhizoctonia solani K¨uhn e Pythium sp. in vitro conditions. The experimental design was completely randomized, with four replications. Beet seeds, tomato and cucumber were submerged in chitosan solution for 20 minutes, in concentrations of 0.25, 0.5, 1 and 2% in the control and distilled water. Seeds were sown in trays containing Plantmax Florestalr substrate sterilized and inoculated with Fusarium sp., Rhizoctonia solani K¨unh and Pythium sp., respectively for the three cultures. The experiment was conducted for 14 days in growth chamber with controlled temperature (25 C 2 C), light (12 hour photoperiod) and humidity (70% 10%). The evaluations were seed emergency, seedling damping-off, seedling length, fresh weight and activity of the enzymes phenylalanine amˆonia-liase (PAL), chitinase and b-1,3-glucanase. It was also rated the mycelial growth of Fusarium sp., Pythium sp. and R. solani on P.D.A. (Potato-Dextrose and Agar) culture medium containing chitosan at the same concentrations evaluated in seeds. For beet growing, seed treatment with chitosan presented higher emergence and the length of the seedlings, and reduced the percentage of tipping. Treatment with chitosan activated the systemic acquired resistance with expression of chitinase and b-1,3-glucanase enzymes. For the tomato crop in chitosan concentration of 0.25% favored the emergency of seedlings, reduced the incidence of tipping and activated the PAL enzymes, chitinase and b-1,3-glucanase. In cucumber on the concentration of up 0.5% favored seedlings emergence and reduces the incidence of tipping. Chitosan activated the PAL enzymes and b-1,3-glucanase. Chitosan also presented fungistatic action on the initial growth of Pythium sp. and R. solani in vitro conditions, however, such action did not prevail until the end of the experiment. To Fusarium sp. the concentration of chitosan resulted in the reduction of mycelial growth in vitro.